A flower‐like α‐phase nickel‐cobalt‐manganese hydroxide modified with two‐dimensional Ti3C2 for high performance hybrid supercapacitors. Issue 4 (9th March 2021) - Zhang, Jiaying; Chen, Hanlin; Chen, Zhi; Li, Chao; Meng, Xianhe; Fan, Meiqiang; Ma, Tingli
Abstract: A flower‐like nickel‐cobalt‐manganese hydroxide (NiCoMn‐OH) modified with two‐dimensional Ti3 C2 nanoflakes has been synthesized via simple one‐step hydrothermal method. The NiCoMn‐OH/Ti3 C2 composite exhibits a high specific capacity of 670.3 C/g at a specific current of 1 A/g, higher than 614.6 C/g for NiCoMn‐OH and 8.9 C/g for Ti3 C2 at the same conditions. The improved electrochemical performance is due to that Ti3 C2 is absorbed and distributed on the surface of NiCoMn‐OH in its situ synthesis process and enhances its electro‐activity. The hybrid supercapacitor based on NiCoMn‐OH/Ti3 C2 and RGO shows high specific capacity of 177.5 C/g at 0.5 A/g and 103.1 C/g at 10 A/g, retaining 93.28% of initial capacity after 5000 charge/discharge cycles at 7 A/g. The hybrid supercapacitor also displays extraordinary specific energy of 41.15 Wh/kg at a specific power of 375 W/kg and 21.46 Wh/kg even at 7.5 kW/kg. Abstract : Herein, we synthesized novel NiCoMn‐OH/Ti3 C2 composites through hydrothermal method. The NiCoMn‐OH/Ti3 C2 //RGO hybrid supercapacitor was assembled, which displays excellent stability of 93.28% after 5000 cycles and can successfully power the LED light.